Seaweed-derived polymeric materials for multiapplications including marine algal cultivation1. Issue 25 (21st March 2015) - Chaudhary, Jai Prakash; Chejara, Dharmesh R.; Eswaran, K.; Meena, Ramavatar; Ghosh, Pushpito K.
<x xml:space="preserve">Abstract</x> This study described the preparation of phycocolloids based polymeric materials for multiapplications including seaweed cultivation in open sea water conditions via grafting reaction of phycocolloids with vinyl acetate (VAc).